KINERJA INDUSTRI KERAJINAN UKIR DI KOTA PALEMBANG - Nazeli Adnan (Department of Development Economics, Universitas Sriwijaya, 2008)
This Research bent on to know characteristic, and performance of crafting industry carves specific Palembang. Data that used is primary and data secondary. Method of data intake uses method of survey with technique of descriptive and quantitative method analysis. Research Result shows characteristic woodcraft industry is seen from education level a large part of SLTP (38,67 percents), SLTA (56,35 percents). Fee is paid every day, every week, and contract and per production. Earnings gyrates Rp.400 thousand Rp600 thousand (38,67 percents). Source Modal 92 percents capital by it self and only 8 percents use debit capital. Job of Number of hours the average of 8 hour every day, meanwhile workday amount 7 day a weeks. Performance of woodcarving crafting industry that seen from productivity, value added, and efficiency shows good enough performance. Such as those which has been discussed at previous part total productivity crafting industry carves as high as 2,52. However if seen from labor productivity only as high as Rp.2.458.523.4 and capital productivity as high as Rp.0,33. Meanwhile seen from value added that can be created by [crafting/ diligence] industry as high as 390, 91 million every year. Other Indicator in seeing performance of crafting industry carves that is mounts efficiency is obtained/got bacillus 1.52. Key Words: Performance, Efficiency, Value Added, Productivity